Comparison of performance between two microcatheter systems in ab externo canaloplasty: A retrospective comparison study. Issue 3 (May 2020) - Vastardis, Iraklis; Kontopoulou, Kalliopi; Fili, Sofia; Gatzioufas, Zisis; Kohlhaas, Markus
Purpose: To compare the performance of two different microcatheter systems, iTrack™ 250A and Glaucolight, in ab externo canaloplasty in three major categories: intraocular pressure reduction, drug therapy reintroduction, and evaluation of viscodilation over distension of the inner wall of Schlemm's canal. Methods: A total of 56 and 46 eyes from different glaucoma types underwent ab externo canaloplasty using two different microcatheter systems. Group formation was made according to microcatheter system used. Kaplan–Meier test was performed for drug therapy reintroduction in relation to the two microcatheters. Tests of between-subject effects in two-way analysis of variance evaluated the efficacy of the two microcatheters and their features in relation to intraocular pressure reduction. Results: Kaplan–Meier test was not statistically significant (p = 0.20) regardless of microcatheter system. Tests of between-subject effects in relation to intraocular pressure reduction was not statistically different between the two microcatheters (p = 0.26) or between microcatheter and follow-up (p = 0.90). Intraocular pressure reduction in different glaucoma type was statistically significant during the follow-up period and glaucoma types showed different results between them in relation to follow-up (p < 0.001 and p = 0.002, respectively), but the pairwise comparison was not statistically important (p = 0.42). Intraocular pressure reduction was better in pseudophakic eyes in comparison with phakic eyes (p = 0.03), but the selection of microcatheter seemed not to affect this result (p = 0.11 and p = 0.32, respectively). Conclusion: Both microcatheter systems performed equal in terms of intraocular pressure reduction. Drug therapy reintroduction was not affected by the selection of the two microcatheters. Different types of glaucoma responded different to canaloplasty. Pseudophakic eyes responded better to treatment than phakic eyes, but the microcatheter selection seemed not affect this result.